Constraining the temperature–density relation of the intergalactic medium with the Lyman-alpha and beta forests - Boera, Elisa; Murphy, Michael T.; Becker, George D.; Bolton, James S. (Oxford University Press, 2016)
The post-reionization thermal state of the intergalactic medium is characterized by a power-law relationship between temperature and density, with a slope determined by the parameter γ. We describe a new method to measure γ using the ratio of flux curvature in the Lyman α and β forests. At a given redshift, this curvature ratio incorporates information from the different gas densities traced by Lyman α and β absorption. It is relatively simple and fast to compute and appears robust against several observational uncertainties. We apply this technique to a sample of 27 high-resolution quasar spectra from the Very Large Telescope. While promising statistical errors on γ appear to be achievable with these spectra, to reach its full potential, the dependence of the curvature ratio on the thermal state of the gas in the foreground Lyman α forest will require further, detailed forward modelling.